Development of acute ischemic stroke and seizure in a patient with COVID-19 disease: A case report (Indian Journal of Case Reports, 2021)
Acute ischemic stroke (AIS) is a life-threatening central nervous system (CNS) complication of coronavirus disease 2019 (COVID-19) infection. Here, we present the case of a 50-year-old COVID-19-positive male who developed AIS with hemorrhagic conversion during treatment in intensive care. He was managed with conservative treatment consisting of deep vein thrombosis prophylaxis and physiotherapy. We delayed oral aspirin and atorvastatin therapy due to hemorrhagic conversion. After 1 month of discharge, the patient presented with a seizure episode. He was observed for 24 h and discharged with prophylactic antiepileptic. Patients with COVID-19 may present with seizure episodes due to viral invasion into CNS, metabolic factors, and other systemic illnesses. Hence, seizures must be considered both as a presenting feature and long-term sequelae of COVID-19 infection. Physicians should take into consideration AIS as a possible complication of COVID-19 infection and should look out for clinical features suggestive of stroke for early diagnosis and improved clinical outcome.